Associations of meeting 24-h movement guidelines with stress and self-rated health among adults: is meeting more guidelines associated with greater benefits? - Kaja Kastelic; Željko Pedišić; Dean Lipovac; Nika Kastelic; Si-Tong Chen; Nejc Šarabon (BMC, 2021)
Abstract Background Several countries have recently issued 24-h movement guidelines that include quantitative recommendations for moderate-to-vigorous physical activity (MVPA), sedentary behaviour (SB), and sleep. This study explored the associations of meeting the 24-h movement guidelines with stress and self-rated health among adults, and whether the likelihood of favourable outcomes increases with the number of guidelines met. Methods A total of 2476 adults aged 18 years and over completed a questionnaire on their time spent in MVPA, SB and sleep, frequency of stress (never, very rarely, occasionally, often, every day), self-rated health (very good, good, fair, bad, very bad), sociodemographic characteristics, and lifestyle variables. Results In an ordinal logistic regression analysis adjusted for age, sex, body mass index, education, socio-economic status, employment, place of residence, living with or without partner, and smoking, lower odds of higher frequency of stress were found for those meeting the combined 24-h movement guidelines (adjusted odds ratio [OR] = 0.45; 95% confidence interval [CI]: 0.32, 0.63; p <  0.001), any combination of two guidelines (OR range: 0.48-0.63; p <  0.05 for all), and sleep guideline only (OR = 0.51; 95% CI: 0.35, 0.75; p = 0.001). Higher odds of better self-rated health were found for those meeting the combined 24-h movement guidelines (OR = 2.94; 95% CI: 2.07, 4.19; p <  0.001), combination of MVPA and SB guidelines (OR = 2.33; 95% CI: 1.57, 3.44; p <  0.001), combination of MVPA and sleep guidelines (OR = 1.78; 95% CI: 1.23, 2.59; p = 0.002), and MVPA guideline only (OR = 2.24; 95% CI: 1.50, 3.36; p <  0.001). Meeting more guidelines was associated with greater odds of favourable outcomes (p for linear trend < 0.001). Conclusion Adults who meet the sleep guideline, any combination of two guidelines, or all three guidelines experience stress less frequently. Meeting the MVPA guideline alone or in combination with any other movement behaviour guideline was associated with better self-rated health. The likelihood of less frequent stress and better self-rated health increases with the number of guidelines met. Adults should be encouraged to meet as many movement behaviour guidelines as possible.